Giant graviton expansion for general Wilson line operator indices - Yosuke Imamura; Akihiro Sei; Daisuke Yokoyama (Journal of High Energy Physics)
Abstract We propose a giant graviton expansion for Wilson line operator indices in general representations. The inserted line operators are specified by power sum symmetric polynomials p λ labeled by partitions λ. We interpret the partitions as the structure of fundamental string worldsheets wrapping around the temporal circle. The strings may or may not end on giant gravitons, and by summing the contributions from all brane configurations consistent with the specified partitions, we obtain the finite N line operator index. The proposed formula is consistent with known results and passes highly non-trivial numerical tests.